2022
DOI: 10.1021/acsnano.2c05069
|View full text |Cite
|
Sign up to set email alerts
|

Self-Healing Hyaluronic Acid Nanocomposite Hydrogels with Platelet-Rich Plasma Impregnated for Skin Regeneration

Abstract: The development of natural hydrogels with sufficient strength and self-healing capacity to accelerate skin wound healing is still challenging. Herein, a hyaluronic acid nanocomposite hydrogel was developed based on aldehyde-modified sodium hyaluronate (AHA), hydrazide-modified sodium hyaluronate (ADA), and aldehyde-modified cellulose nanocrystals (oxi-CNC). This hydrogel was formed in situ using dynamic acylhydrazone bonds via a double-barreled syringe. This hydrogel exhibited improved strength and excellent s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(65 citation statements)
references
References 66 publications
1
64
0
Order By: Relevance
“…However, most of the platelet-rich plasma used in the clinic is liquid, which cannot be fixed in the local area, and the growth factors in platelet-rich plasma is released too fast to maintain the long-term effective concentration. Recently, it has been reported that the plasma-rich gel is an effective carrier to protect platelet growth (Li et al, 2022a).…”
Section: Other Considerationsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, most of the platelet-rich plasma used in the clinic is liquid, which cannot be fixed in the local area, and the growth factors in platelet-rich plasma is released too fast to maintain the long-term effective concentration. Recently, it has been reported that the plasma-rich gel is an effective carrier to protect platelet growth (Li et al, 2022a).…”
Section: Other Considerationsmentioning
confidence: 99%
“…However, most of the platelet-rich plasma used in the clinic is liquid, which cannot be fixed in the local area, and the growth factors in platelet-rich plasma is released too fast to maintain the long-term effective concentration. Recently, it has been reported that the plasma-rich gel is an effective carrier to protect platelet growth ( Li et al, 2022a ). In vivo studies showed that the hydrogel significantly promotes the healing of full-thickness skin wounds by enhancing granulation tissue formation, promoting collagen deposition and accelerating re-epithelialisation and neovascularisation.…”
Section: Application Of a Nanocomposite Hydrogel Delivery System To D...mentioning
confidence: 99%
See 1 more Smart Citation
“…The supramolecular interaction is a general term for a class of intermolecular interactions . The supramolecular interactions mainly include hydrophobic interactions, host–guest interactions, hydrogen bonds, crystallization, electrostatic interactions, and multiple intermolecular interactions. These interactions exist between molecules, oligomers, or polymer chains. Compared to traditional chemical cross-linking hydrogels, the supramolecular hydrogel with self-healing properties has extremely outstanding advantages in the clinical wound management field.…”
Section: Introductionmentioning
confidence: 99%
“…Natural polymer hydrogels with good biocompatibility and biodegradation can support cell adhesion, proliferation, and differentiation on its surface or inside. Thus, they are often used in the field of tissue engineering, for example, in cartilage repair and skin dressing [ 3 , 4 , 5 , 6 ]. However, their applications were hindered due to most natural polymers’ poor strength and toughness.…”
Section: Introductionmentioning
confidence: 99%